Dynamic group key management scheme for homogeneous wireless sensor networks - Tao WEN; Yong ZHANG; Quan GUO; Feng-kun LI (Tongxin xuebao)
Focuses on the study of GKM scheme applicable to homogenous network model，proposed a clear and complete key management model for dynamic groups for the first time and exposed a dynamic group key management(DGKM)scheme based on symmetric polynomials.The scheme provided a solution to related group key management issues,such as key establishment,key updating,node addition and node revocation,for a multicast group consisting of any number(bigger than 2 and less than the total number)of nodes.Besides,the scheme supported node mobility as well as scalability and coped well with the unreliable wireless multicast communication.Group members can get group key by computing and with little wireless communication,therefore,greatly reduced the cost of key agreement.The analysis shows the scheme has very good performance in terms of storage,computation as well as communication and is more suitable to wireless sensor networks with limited capability.